LETTER TILES TO TEACH SPELLING: HOW DOES IT WORK? - Elita Elva Lintang Femila; Arliva Ristiningrum (International Conference on Education and Language (ICEL), 2016)
This research aims at describing a new experience or concept about teaching spelling using letter tiles. Letter tiles are a set of alphabet, which contains of vowels and consonants, and they have different colors which can make students more fun to learn. Spelling is one of literacy skills that students have to be mastered, and this is the first step to mastering the major skills. The subjects of the research were the fourth grade students of elementary school. There were 50 students. The instrument used in the research was an English spelling test. The test was divided into two parts. They were the pre-test and post-test. Before the instrument was implemented, there was a try-out first. The result of the try-out was used to find out the validity and reliability of the test which was calculated by using SPSS conducted by using a computer program. The result of the analysis show that the mean scores of pre-test is higher that post-test, i.e. 33.63>29.31. Moreover, the T-test result shows that the t0 is higher than the tt, i.e. 3.167>1.677. It can be concluded that there is a significant difference between the score of the students who are taught by using letter tiles and those who are not taught by using letter tiles.